Unsuspected Xp11 Translocation Renal Neoplasm Associated With Contralateral Clear Cell Carcinoma. (May 2016) - D'Antonio, Antonio; Addesso, Maria; Nappi, Oscar; Zeppa, Pio
In this report, we present for the first time the coexistence of a conventional renal cell carcinoma (RCC) and an undefined Xp11 translocation renal neoplasm in distinct kidneys, which was difficult to definitively classify as either carcinoma or PEComa (perivascular epithelioid cell tumor). While one of the tumors showed the morphological and immunohistochemical features of clear RCC, the other had an unusual morphology with a prominent nested pattern. Microscopically this tumor showed nests of cells with clear and eosinophilic cytoplasm and nuclei with prominent nucleoli; some hyaline globules were evident. Immunohistochemical panel showed negativity for cytokeratin-pan, cytokeratin-7, PAX8, and CD10 but positive immunostaining for cathepsin K, racemase, Melan-A, and TFE3. A subsequent, metaphase, dual-color fluorescence in situ hybridization confirmed the Xp11 translocation. Attention should be paid to the routine immunohistochemical profile that, in case of negativity of specific RCC markers, may suggest an Xp11 translocation renal tumor. The addition of TFE3 can easily identify the specific subtype.